Masjid Besi, Putrajaya: Rekabentuk dan hubungannya dengan senibina Islam - Mohd Zain, Noorzahidah; Rosland, Anitha; Ab Halim, Asyiqin; Abdul Hamid, Faisal @ Ahmad Faisal (2014)
Masjid Tuanku Mizan Zainal Abidin also known as Masjid Besi located in Precint 3, Putrajaya, Malaysia is built based on design modern contemporary and Islamic architecture.This mosque is the one only mosque which uses 6000 tonnes of steel or 70 percent building material during the construction, thus it is known as Masjid Besi. This study found that, this masjid is not one hundred percent based on Islamic architecture because is it more incline to modern design.Therefore, this paper will discuss the design of the Masjid Besi design architecture, by examining the relationship Islamic architectural with other elements influences exist on mosque architecture.